Penerapan Forward Chaining Dalam Pengembangan Simulasi Gamifikasi Interaktif Untuk Pelatihan Operasional Logistik Menggunakan Unity - Sulaksono, Al Novianti Ramadhani; Prianto, Cahyo; Nurkamal Fauzan, Mohamad (Institut Teknologi Garut, 2025)
Workforce training in the logistics sector requires an interactive approach capable of realistically representing the complexity of operational processes. This study aims to develop a logistics training system based on gamified simulation using Unity, integrated with a forward chaining inference method. The system was designed using the ADDIE development model and applies IF–THEN logic rules as the foundation for automatic evaluation of user decisions.An application named SIMBA was developed across four training levels, incorporating gamification elements such as points, badges, leaderboards, and tiered challenges. Evaluation involving 30 respondents was conducted using a five-point Likert scale questionnaire designed to measure the effectiveness of gamification elements and user experience. The assessment instrument met reliability and validity criteria based on Cronbach’s Alpha, Average Variance Extracted (AVE), and Composite Reliability (CR). Test results showed a Cronbach’s Alpha value of 0.896, AVE ranging from 0.777 to 0.869, and CR between 0.913 and 0.952, indicating excellent consistency and reliability.These findings demonstrate that forward chaining is effective as a rule-based evaluation mechanism in simulation-based digital training, and suggest that similar approaches can be adapted for simulation-based training in other industrial sectors. The original contribution of this research lies in the comprehensive integration of forward chaining and gamification within logistics simulation training—an approach that has been rarely implemented in prior studies.